Assessing the impact of COVID-19 on rural women and men in Kenya - Food and Agricultural Organization of the United Nations; United States Agency for International Development; International Food Policy Research Institute; Alvi, Muzna; Gupta, Shweta; Barooah, Prapti; Bryan, Elizabeth; Mawia, Harriet; Ringler, Claudia (Food and Agricultural Organization of the United Nations, 2021)
The first wave of COVID-19 cases occurred between June and August 2020. A second wave occurred between October and December 2020 and by the end of December 2020, the number of COVID-19 cases was 92 459. The third rise in cases occurred between January and March of 2021 and partial lockdowns were reimposed in the most affected counties of the country, including mobility restrictions and curfews. This brief releases data on the gender impacts of the COVID-19 pandemic on rural households/livelihoods and the agricultural sector in Kenya.